Seeing and thinking groups: embodied foundations of perceptual and social structuring - Razpurker-Apfeld, Irene (Frontiers in Language Sciences, 2025)
The processes of perceptual organization and social categorization share the goal of simplifying and structuring the world, though they have traditionally been studied within separate branches of psychology. Drawing on embodied cognition, this perspective suggests that both processes stem from bodily experiences. Early sensorimotor experiences, such as being held in proximity or rocked in synchrony, may have shaped the principles of perceptual organization and provide the foundations for social categorization. To integrate these domains, a triadic embodied model is proposed, linking bodily experience, perceptual organization, and social categorization as dynamically interacting vertices. The model allows bidirectional influences, whereby each element can prime and reinforce the others, and may also involve activation of metaphorical concepts. It further explains how cultural context can bias these interconnections. The model situates social categorization along a continuum of representational depth, from shallow symbolic tagging to deep embodied simulation. While prior work has demonstrated dyadic links between bodily experience, perceptual organization, and social categorization, the present article explicitly integrates these domains in a unified model, offering new directions for understanding how people structure their physical and social world.